Transcriptome analysis reveals salivary gland-specific neuropeptide signaling genes in the predatory stink bug, Picromerus lewisi - Li, Wenhong; Li, Zhimo; Yang, Xiang; Wang, Xinyi; Yang, Mingwei; Huang, Chunyang; He, Yueping (Frontiers in Physiology, 2023)
Predatory stink bugs derive from phytophagous stink bugs and evolved enhanced predation skills. Neuropeptides are a diverse class of ancient signaling molecules that regulate physiological processes and behavior in animals, including stink bugs. Neuropeptide evolution might be important for the development of predation because neuropeptides can be converted to venoms that impact prey. However, information on neuropeptide signaling genes in predatory stink bugs is lacking. In the present study, neuropeptide signaling genes of Picromerus lewisi, an important predatory stink bug and an effective biological agent, were comprehensively identified by transcriptome analysis, with a total of 59 neuropeptide precursor genes and 58 potential neuropeptide receptor genes found. In addition, several neuropeptides and their receptors enriched in salivary glands of P. lewisi were identified. The present study and subsequent functional research contribute to an in-depth understanding of the biology and behavior of the predatory bugs and can provide basic information for the development of better pest management strategies, possibly including neuropeptide receptors as insecticide targets and salivary gland derived venom toxins as novel killing moleculars.